Strength training for women: Debunking myths that block opportunity - Ebben, W. P.; Jensen, L. J. (The Physician and Sportsmedicine, 1998)
Traditional gender roles and differences in absolute strength have resulted in misconceived approaches to strength training for women. Male physiology, more than hormones, explains men's superior absolute strength. When other measures of strength are used, such as strength relative to cross-sectional area of muscle, the strength of men and women is nearly equal. Women who practice the same well-designed strength training programs as men benefit from bone and soft-tissue modeling, increased lean body mass, decreased fat, and enhanced self-confidence.